The Traditional Medicinal Plants Cuphea Calophylla, Tibouchina kingii, and Pseudelephantopus spiralis Attenuate Inflammatory and Oxidative Mediators (2018)
ABSTRACT: Aerial parts of Cuphea calophylla, Tibouchina kingii, and Pseudelephantopus spiralis have been used in Colombian traditional medicine for inflammation. However, the underlying mechanisms that could explain the anti-inflammatory actions remain unknown. This study aimed to elucidate the anti-inflammatory and cytoprotective effects of hydroalcoholic extracts from C. calophylla (HECC), T. kingii (HETK), and P. spiralis (HEPS) in LPS-stimulated THP-1 macrophages. Reactive oxygen species (ROS), nitric oxide (NO), and malondialdehyde (MDA) were monitored as inflammatory and oxidative markers. The inhibition of lipoxygenase (LOX) and cyclooxygenase (COX) activities in a cell-free system were also investigated. Antioxidant activities were determined using standard in vitro methods. All extracts inhibited the NO, ROS, and MDA levels. HETK showed the highest ROS production inhibition and the highest antioxidant values, whereas HETK and HEPS significantly decreased the cytotoxicity mediated by LPS. The release of MDA was reduced significantly by all extracts. Moreover, the catalytic activity of LOX was inhibited by HECC and HETK. HECC was a more potent reducer of COX-2 activity. All extracts effectively suppressed COX-1 activity. In summary, these results suggest that HECC, HEPS, and HETK possess anti-inflammatory properties. Therefore, these plants could provide a valuable source of natural bioactive compounds for the treatment of inflammatory-related diseases.